Advances in Alzheimer's disease's pharmacological treatment - Carlos Elias Conti Filho; Lairane Bridi Loss; Clairton Marcolongo-Pereira; Joamyr Victor Rossoni Junior; Rafael Mazioli Barcelos; Orlando Chiarelli-Neto; Bruno Spalenza da Silva; Roberta Passamani Ambrosio; Fernanda Cristina de Abreu Quintela Castro; Sarah Fernandes Teixeira; Nathana Jamille Mezzomo (Frontiers Media S.A., 2023)
Alzheimer's disease (AD) is the most common type of dementia in the elderly. Several hypotheses emerged from AD pathophysiological mechanisms. However, no neuronal protective or regenerative drug is available nowadays. Researchers still work in drug development and are finding new molecular targets to treat AD. Therefore, this study aimed to summarize main advances in AD pharmacological therapy. Clinical trials registered in the National Library of Medicine database were selected and analyzed accordingly to molecular targets, therapeutic effects, and safety profile. The most common outcome was the lack of efficacy. Only seven trials concluded that tested drugs were safe and induced any kind of therapeutic improvement. Three works showed therapeutic effects followed by toxicity. In addition to aducanumab recent FDA approval, antibodies against amyloid-β (Aβ) showed no noteworthy results. 5-HT6 antagonists, tau inhibitors and nicotinic agonists' data were discouraging. However, anti-Aβ vaccine, BACE inhibitor and anti-neuroinflammation drugs showed promising results.